Moniker: Etymology and Lexicographical History - Sayers, William (Miscelánea: A Journal of English and American Studies, 2013)
Popular language presents special difficulties for the lexicographer and etymologist, professional and amateur. Moniker ‘nickname, alias’ has found numerous explanations, none convincing. The term is traced to Old Irish ainm ‘name’, subsequently adopted, through well established patterns for encryption, into Shelta, the language of the Irish travelers. Its spread in North America and Australia may have been furthered by the itinerant life-styles of men seeking employment.
Keywords: moniker; Irish travelers; Shelta; popular language